HISTORY AND THE CHARACTERISTICS OF THE FINANCE. TYPICAL ANALYSIS ON THE FINANCE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Finance is a term for matters regarding the management, creation, and study of money and investments. It involves the use of credit and debt, securities, and investment to finance current projects using future income flows. Because of this temporal aspect, finance is closely linked to the time value of money, interest rates, and other related topics.